Inovasi Metode Pembelajaran PAI Sebagai Upaya Meningkatkan Prestasi Belajar Siswa di Alkhairaat Labuha - Amanan Sulaiman (IAIN Ternate, 2016)
Recognized that the implementation of learning PAI. In many schools still meet obstacles, therefore the need for innovation method or way of learning, With the innovative method of learning expected of teachers is not as if a single source of information. Teachers are able to innovate in teaching methods open up horizons of students to be innovative and creative. Through innovative teaching methods, learning atmosphere in the classroom is not stuck in an atmosphere of rigid and monotonous. So that students can easily understand the material presented. Susana will make student learning unsaturated received materials from the teacher. Therefore, the authors are interested to study